2020
DOI: 10.3390/ma13061264
|View full text |Cite
|
Sign up to set email alerts
|

Third Body Wear of UHMWPE-on-PEEK-OPTIMA™

Abstract: PEEK-OPTIMA™ is being considered as an alternative to cobalt chrome (CoCr) in the femoral component of total knee replacements. To date, investigations of ultra-high molecular weight polyethylene (UHMWPE)-on-PEEK have shown an equivalent wear rate to conventional implant materials under standard conditions. In this study, the third body wear performance of UHMWPE-on-PEEK was directly compared to UHMWPE-on-CoCr in a series of pin-on-plate studies using two approaches for third body damage. Damage simulation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…[1][2][3][4] Furthermore, due to their good wear resistance, PEEK, and carbon fiber reinforced PEEK (CFR-PEEK) have been studied as articulating surface materials for artificial joints. 5,6 Although they have been extensively investigated, the delamination resistance of PEEK materials still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, due to their good wear resistance, PEEK, and carbon fiber reinforced PEEK (CFR-PEEK) have been studied as articulating surface materials for artificial joints. 5,6 Although they have been extensively investigated, the delamination resistance of PEEK materials still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric material is a soft material that gradually wears out during the operation process. Hence, a significant influence on the durability of the tribological system in which the friction pair consists of a polymeric part and a ceramic part is that of the ceramic part and its surface topography characteristics [ 1 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous mechanical testing indicated that gross loosening of a PEEK femoral component is very unlikely if the fixation surface has been optimized to provide sufficient mechanical interlock [ 26 ]. However, micromotions of a loosened implant could cause abrasion of the cement–implant interface leading to the subsequent release of PEEK and/or cement particles, which may accelerate wear debris induced osteolysis and/or lead to failure of the cement mantle and could produce cement particles leading to third-body wear [ 29 , 30 ]. These potential complications underline the importance of understanding the implant–cement interface, particularly for a PEEK femoral TKA component.…”
Section: Introductionmentioning
confidence: 99%